Study on regionalization of rice yield estimation by remote sensing in Zhejiang provice - XU Hong-wei; WANG Ren-chao (浙江大学学报. 农业与生命科学版, 2000)
From the characters of yield estimation by remote sensing, based on analyzing the natural conditions of Zhejiang province, division index in which planting system is the main one are determined. The regionalization of rice yield estimation by remote sensing in Zhejiang province is studied by space neighboring analysis in GIS combined with tree algorithm, and the results are satisfied.